PENGEMBANGAN KREATIVITAS ANAK ASUH BERBASIS TI DALAM MENANAMKAN NILAI WIRAUSAHA PADA ASRAMA PUTERA PANTI ASUHAN YATIM PIATU DAN DHU’AFA YAYASAN AL-ASHR BANJARMASIN - Erfan Karyadiputra; Galih Mahalisa; Abdurrahman Sidik; Muhammad Rais Wathani (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2019)
The problems faced by the children of Banjarmasin Al-Ashr Orphanage are almost the same as those faced by other orphanages in the city of Banjarmasin, namely, lack funds and personnel or volunteers who help and guide orphanage children to develop their skills and creativity as a provision in carrying out life after the completion of the orphanage. The purpose of this community service program is to make the children of the Al-Ashr Orphanage have a strong and more independent motivation by providing them with the knowledge and skills they will use to prepare themselves for the future. While the target of this activity is to make the children of the Al-Ashr Orphanage have design skills in making invitations, brochures, and banners as well as online businesses. The method used is training and guidance, where training is carried out with presentations and practices.